2018
DOI: 10.1007/s00170-018-2836-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the forming characteristics for Cu/Al bimetal tubes produced by the spinning process

Abstract: Tube spinning technology represents a process with high forming precision and good flexibility and is increasingly being used in the manufacture of bimetal composite tubular structures. In the present study, a forming analysis of clad tube and base tube in spinning process was conducted through numerical simulations and experiments. There was an equivalent stress transition on the interface since the stress transmission was retarded from clad tube to base tube. The yield strength became a main consideration du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A forming analysis of clad tube and base tube in spinning process was conducted by numerical simulations and experiments. The results indicated that as the press amount (δ) increased, the strain of clad tube changed more than base tube and as the feed rate increased, the strain decreased in axial direction and tangential direction but almost unchanged in radial direction [15]. The spin forming parameters of bimetallic composite pipe were optimized by FEM and experiment in my previous research, and the torque and the residual contact pressure were analyzed during forming process.…”
Section: Introductionmentioning
confidence: 98%
“…A forming analysis of clad tube and base tube in spinning process was conducted by numerical simulations and experiments. The results indicated that as the press amount (δ) increased, the strain of clad tube changed more than base tube and as the feed rate increased, the strain decreased in axial direction and tangential direction but almost unchanged in radial direction [15]. The spin forming parameters of bimetallic composite pipe were optimized by FEM and experiment in my previous research, and the torque and the residual contact pressure were analyzed during forming process.…”
Section: Introductionmentioning
confidence: 98%
“…Bimetallic materials generally have superior comprehensive properties which are extremely di cult to achieve for single metal materials [1][2][3]. Comparing to other bimetal bonding processes, the solid-liquid bimetal compound casting has been extensively used in modern industry with the advantages of good interfacial bonding quality, high production e ciency and wide range of applicable alloys, etc.…”
Section: Introductionmentioning
confidence: 99%
“…During the experiment the bonding strength of the Al/Fe bi-metal pipes was described, on the basis of which the signi cant process parameters were determined, including the radial gap, discharging voltage, and feeding length. Jin [10] analysed the forming characteristic of the Cu/al bi-metal pipes, i.e. a clad pipe and a base pipe, that emerged during the spinning process using a variety of simulations and experiments.…”
Section: Introductionmentioning
confidence: 99%